KEMAMPUAN MENYELESAIKAN SOAL CERITA MATERI BANGUN DATAR SEGI EMPAT BERDASARKAN TINGKAT KEMAMPUAN SISWA DI SMP - Husna Husna; Agung Hartoyo; Bistari Bistari (Universitas Tanjungpura, 2020)
AbstractThe purpose of this study is to provide an overview of the ability to solve rectangular flat matter material based on the ability of students in grade VIII of SMP Negeri 9 Pontianak. Based on these objectives, the appropriate method used in this research is descriptive method. The form of research used is a survey. To obtain the data needed in this study, the instrument used was in the form of tests of the ability to solve rectangular flat figure building questions and interviews. The results showed that the students' ability in completing rectangular flat matter material story problems as a whole was based on their ability level, namely for group students on the ability to solve mathematical story problems classified as high, for middle group students the ability to solve mathematical story problems was classified as moderate, for lower group students the ability to solve mathematical story problems is moderate. The ability to solve students' flat story matter questions in quadrilateral according to their level of ability. But overall it can be seen that the ability to solve story problems is classified as moderateKeywords: Ability To Solve Story Problems, Rectangular Flat shape, Ability Level